Pembangunan Mandi Cuci Kakus (MCK) Sebagai Bentuk PKM Sosial Budaya dan Lingkungan Desa Bulakan Kota Cilegon - Juhandi Juhandi; Joni Prihatin; Riky Destian Husada; Vika Rahma Zein Nissa; Ahmad Irgy Syahreza (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The social culture and environment in one region differ from each other, depending on geography and the people who inhabit that place. It is not impossible that problems in this area can be experienced by these human members. One of them is in the Bulakan Village area where there are still areas that do not have toilets or toilets for short. The habit of residents who still carry out these activities in their backyard has become the concern of the 42 KKM group of Bulakan Village, Bina Bangsa University. The aim of PKM in the Social, Cultural and Environmental sector is to build a MCK in the house of one of the residents in Bulakan Village. The method used is survey and implementation of PKM. It is hoped that the results of the PKM in the field of Socio-Cultural and Environmental Affairs in building toilets can be used by local residents, so that the habit of defecating, washing and bathing is no longer carried out around the house because it will cause disease for residents of the surrounding area.